2019
DOI: 10.3390/en12091678
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Optimal Demand Response Control and Thermal Energy Storage on a District Heating System

Abstract: Demand response has been studied in district heating connected buildings since the rollout of smart, communicating devices has made it cost-effective to control buildings’ energy consumption externally. This research investigates optimal demand response control strategies from the district heating operator perspective. Based on earlier simulations on the building level, different case algorithms were simulated on a typical district heating system. The results show that even in the best case, heat production co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…However, they stated that the findings also reflect the need for development of DH pricing models to make the demand side management more attractive to DH customers. Similar results were also reported by Romanchenko et al in [18], where the cost savings achieved were approximately 1%, and Salo et al in [17], whose simulated results showed that even in the best case, heat production costs can be decreased by only 0.7%. All studies mentioned above have reported cost savings to be low.…”
Section: Economic Feasibility Of the Studied Dr System From Stakeholdsupporting
confidence: 89%
See 3 more Smart Citations
“…However, they stated that the findings also reflect the need for development of DH pricing models to make the demand side management more attractive to DH customers. Similar results were also reported by Romanchenko et al in [18], where the cost savings achieved were approximately 1%, and Salo et al in [17], whose simulated results showed that even in the best case, heat production costs can be decreased by only 0.7%. All studies mentioned above have reported cost savings to be low.…”
Section: Economic Feasibility Of the Studied Dr System From Stakeholdsupporting
confidence: 89%
“…To achieve some effect in heat production by controlling the DR, there must be a lot of power within the DR, which means there is a need for a number of buildings using a DR service. A redeeming feature is that the DR usage level can be quite high as the residential buildings store heat well, which means that the mass of the building cools down slowly [13,[16][17][18][19][20][21]. It can be seen in the field test that a couple of hours without heating do not have any notable effect on indoor air conditions, and with the help of DR production can be optimized during as much as 33 percent of the day without causing discomfort to customers.…”
Section: Smart Interaction Between Buildings and Energy System Emissionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction of heat loss in heating networks can also be achieved by using thicker layers of thermal insulation or heating networks with a lower thermal conduction coefficient of thermal insulation, which is associated with a higher cost of heating networks. Heat exchange in single pre-insulated heating networks, which are the most commonly used, has been thoroughly studied [7][8][9][10][11]. Heat losses in single pre-insulated pipes can be determined using analytical methods [3,7,9,12,13] as well as using numerical methods in two-dimensional [10,12] and three-dimensional [14] problems.…”
Section: Introductionmentioning
confidence: 99%